The Relationship Between School Well-Being and Student Discipline Behavior: Hubungan Antara School Well-Being dan Perilaku Disiplin Siswa - Ella Ameliya Fitril; Lely Ika Mariyati (Academia Open, 2023)
General Background school well-being is crucial for fostering a positive educational environment and promoting student discipline. Specific Background this study investigates the relationship between school well-being and student discipline behavior at a high school. Knowledge Gap while existing research highlights the importance of both constructs, there is limited empirical evidence examining their correlation, particularly in the context of high school students. Aims the research aims to determine whether a significant relationship exists between school well-being and student discipline behavior among students at SMA Avisena. Results analysis revealed a correlation coefficient (rᵪᵧ) of 0.025 with a significance value of 0.747, indicating no significant relationship between the two variables. Despite the absence of a clear correlation, there appears to be a tendency for a connection. Novelty this study contributes to the literature by exploring the dynamics of school well-being and discipline in a high school setting, providing insights into the complexities of student behavior. Implications the findings suggest that while school well-being may not directly influence student discipline behavior, understanding the nuances of their relationship can inform strategies to improve both constructs within educational institutions. Further research is recommended to explore other factors that may mediate or moderate this relationship. Highlights: No significant relationship found between school well-being and student discipline. The study highlights a tendency for a connection despite statistical insignificance. Insights can inform strategies for improving student behavior and well-being. Keywords: School Well-Being, Student Discipline, Correlation, High School, Education